A systematic review and meta-analysis of the globally reported International Classification of Diseases to Perinatal Mortality (ICD-PM) - Kumsa, Henok; Mislu, Esuyawkal; Yimer, Nigus Bililign (Frontiers in Medicine, 2024)
Introduction: Accurate recording and identification of perinatal mortality causes are crucial to reduce the global burden of perinatal mortality through targeted interventions. However, existing International Classifications of Diseases to Perinatal Mortality (ICD-PM) studies are limited with inconsistent results and variations by gestational age. Thus, this review aims to synthesize and document updated data on causes of deaths using ICD-PM classification.Methods: Electronic databases such as PubMed via MEDLINE, SCOPUS, Web of Sciences, EMBASE, Cochrane Library, and PROSPERO were searched to retrieve studies published from 2016 to February 2024. The Newcastle-Ottawa Scale was used to assess the quality of included studies, and heterogeneity between the studies was assessed using I 2 statistic. ICD-PM coded reported data were extracted to Microsoft Excel, and aggregate data of frequencies and percentages were reported.Results: Out of the 23 included studies, 48,596 perinatal mortalities were reported and nearly 96% (46,816 deaths) were classified according to the ICD-PM. The pooled rate of stillbirths in highincome countries was 23/1000 births, in low-income countries was found to be nearly twice as high-income countries. Regarding category of deaths, 25,563 (54.6%) deaths were recorded in antepartum period, and more than half 14,887 (58.2%) were classified under unspecified causes (A6). Moreover, 6,148 (13.7%) and 14,835 (31.7%) deaths were coded with intrapartum and neonatal period causes, respectively. The leading causes of perinatal mortality during the intrapartum was acute intrapartum events (I3) 3712 (57.8%). Further, for neonatal death were low birth weight and prematurity (N9) 4,091 (27.6%) and congenital malformations, deformations, and chromosomal abnormalities (N1) 2,512(16.9%).Congenital malformations, deformations, and chromosomal abnormalities contribute to one in every 10 perinatal deaths and one in every four neonatal deaths. Other specified antepartum disorders are responsible for over half of antepartum deaths, while acute intrapartum events are the leading cause of intrapartum deaths, with a significant proportion remaining unexplained. Maternal complications related to placenta, membranes, cord, labor, and delivery play a significant role in antepartum and intrapartum deaths. Targeted interventions and improved monitoring of high-risk pregnancies are crucial to reduce perinatal mortality rates. Further investigation is needed to enhance understanding and address unexplained perinatal deaths.